Teknik Penarikan Sampel Pada Data Atribut Untuk Pemeriksaan Hasil Akhir Produksi - Ernaning Widiaswanti (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
Final inspection for acceptance or rejection of a product is required by the company before the products are distributed to consumers. Sinar Angkasa Rungkut I, Ltd. Surabaya is a company that produces light. Referring to product quality control, sampling technique is one of methods that can be used to perform inspection in sealex lights process which is seen from bulbs and seals condition. The purpose of this study is to determine the acceptance sampling technique which is suitable for the final inspection of production for the company. From the second sampling which has been used, for sequential sampling result is much better than a single sampling, because the results of sequential sampling calculations give a smaller sample size. In addition, the probability of acceptance (Pa) resulting from sequential sampling produces exactly the same value with the producer and consumer risks defined, namely 0.95 and 0.10.